Activation of Mitochondrial Unfolded Protein Response in SHSY5Y Expressing APP Cells and APP/PS1 Mice - Shen, Yang; Ding, Mao; Xie, Zhaohong; Liu, Xiangtian; Yang, Hui; Jin, Suqin; Xu, Shunliang; Zhu, Zhengyu; Wang, Yun; Wang, Dewei; Xu, Linlin; Zhou, Xiaoyan; et al. (Frontiers in Cellular Neuroscience, 2020)
Alzheimer disease (AD) is the most common form of dementia. Amyloid beta peptide (Aβ) deposition is a major neuropathologic feature of AD. When unfolded or misfolded proteins accumulate in mitochondria, the unfolded protein responses (UPRmt) is initiated. Numerous lines of evidence show that AD pathologenesis involves mitochondrial dysfunction. However little is known about whether the UPRmt is engaged in the process of AD development. In this study, we investigated the UPRmt in mouse and cell models of AD. We found that UPRmt was activated in the brain of 3 and 9 months old APP/PS1 mice, and in the SHSY5Y cells after exposure to Aβ25-35, Aβ25-35 triggered UPRmt in SHSY5Y cells could be attenuated upon administration of simvastatin or siRNA for HMGCS-1 to inhibit the mevalonate pathway, and or upon knocking down SPTLC-1 to lower sphingolipid biosynthesis. We observed that inhibition of UPRmt aggravated cytotoxic effects of Aβ25-35 in SHSY5Y cells. Our research suggests that the UPRmt activation and two pathways necessary for this response, and further provides evidence for the cytoprotective effect of UPRmt during AD process